Sistem Pinjaman Berbunga (Célong Séng Bunga) Dalam Pemenuhan Perjanjian Berdasarkan Kearifan Lokal Di Manggarai Timur - Nataly Silviana Dewi; Stefanus Don Rade (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2024)
This study analyzes the legal relationship of engagement to local wisdom in East Manggarai district. The method used in this research is a qualitative approach whose data collection is through observation and interviews. The purpose of this study was to find the relationship between the law of engagement and the local wisdom of providing interest-bearing loans (Célong Séng Bunga) in East Manggarai district. The existence of engagements and guarantees in providing loans to people in need is the basis of the existence of this zinc interest celong system, but in the past the community still did not know that there was a connection between the activities of this zinc flower celong with the engagement and guarantees contained in the Civil Code. With the zinc celong system, this interest on lending and borrowing helps local communities in fulfilling the agreements they make. Interest-Bearing Loan System, Agreement Fulfillment, Local Wisdom